1992
DOI: 10.1093/clinchem/38.11.2313
|View full text |Cite
|
Sign up to set email alerts
|

Bone-Resorption Markers Galactosyl Hydroxylysine, Pyridinium Crosslinks, and Hydroxyproline Compared

Abstract: We compared the clinical performances of four bone-resorption (BR) assays (hydroxyproline, HYP; galactosyl hydroxylysine, GHYL; deoxypyridinoline, DPD; and pyridinoline, PYD) in subjects with different BR rates: normal (adult men and premenopausal women), mildly increased (postmenopausal osteoporotic women), high (Paget disease patients), and very high (children). The discrimination power (Z score) and the accuracy (estimated by receiver-operating characteristic analysis) for GHYL, DPD, and PYD were compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
21
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(24 citation statements)
references
References 0 publications
3
21
0
Order By: Relevance
“…Although Pyr is known to occur in a variety of connective tissues, Dpyr is thought to be more specific for the type I collagen present in bone. Both compounds are likely to be more specific biochemical markers of bone resorption than serum tartrate-resistant acid phosphatase (TRAP) and urinary Hypro, and of similar specificity to galactosylhydroxylysine [1,2]. They are excreted in the urine in the free and conjugated form and are usually measured by high-performance liquid chromatography (HPLC) [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Although Pyr is known to occur in a variety of connective tissues, Dpyr is thought to be more specific for the type I collagen present in bone. Both compounds are likely to be more specific biochemical markers of bone resorption than serum tartrate-resistant acid phosphatase (TRAP) and urinary Hypro, and of similar specificity to galactosylhydroxylysine [1,2]. They are excreted in the urine in the free and conjugated form and are usually measured by high-performance liquid chromatography (HPLC) [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…A number of markers of bone collagen analysed in serum and urine samples have been used in the clinical evaluation of patients with osteoporosis [1][2][3][4][5][6]. However, the sensitivity and specificity of these markers in assessing bone formation and resorption in relation to bone structure and quality in elderly subjects remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Skin, as an important source of type I collagen, does not contain either of these cross-links [18]. Recent studies have shown that the urine concentrations of Pyr and Dpyr increase in patients with primary hyperparathyroidism, Paget's disease [19][20][21], postmenopausal osteoporosis [1][2][3]22] and fractures [23,24], all of which may involve an increased rate of bone turnover.…”
Section: Introductionmentioning
confidence: 99%
“…As bone is resorbed by osteoclastic activity, the degraded crosslinks of mature collagen, termed pyridinium crosslinks, are excreted in the urine. The urinary pyridinium crosslinks, pyridinoline (Pyd) and deoxypyridinoline (Dpd), provide an excellent framework to infer bone resorption (38)(39)(40)(41)(42)(43)(44)(45)(46). Pyd and Dpd are found in bone and cartilage, but bone has the highest content of Dpd (42,43,46).…”
mentioning
confidence: 99%
“…The urinary pyridinium crosslinks, pyridinoline (Pyd) and deoxypyridinoline (Dpd), provide an excellent framework to infer bone resorption (38)(39)(40)(41)(42)(43)(44)(45)(46). Pyd and Dpd are found in bone and cartilage, but bone has the highest content of Dpd (42,43,46). We previously reported that individuals with NF1 have increased markers of bone resorption (47) and osteoclasts have been shown to be hyperactive in NF1 (10,48).…”
mentioning
confidence: 99%